The loomweaving art of the Mandaya tribe (Manila National Commission of Culture and the Arts, 1998)
Presents step-by-step procedure of the Dagmay, the art of the handloom weaving of the Mandaya tribe.
VHS format.
Keywords: Mandaya; Hand weaving; Handlooms -- Davao Oriental